SOME WAYS IN WHICH THE SCHOOL CLASSROOM ENTERS INTO CHANGES MUSICAL MEANINGS (American Journal of Pedagogical and Educational Research, 2022)
This article considers some ways in which the school classroom enters into, changes and complicates musical meanings, focusing particularly on the role of popular music and how it relates to classical music. I suggest that in bringing popular music into the curriculum, educators have largely ignored the informal learning practices of popular musicians. Popular music has therefore been present as curriculum content, but its presence has only recently begun to affect our teaching strategies. I examine how the adaptation of some informal popular music learning practices for classroom use can positively affect pupils’ musical meanings and experiences. This applies not only to the sphere of popular music, but also to classical music and, by implication, other musics as well. Finally, the notions of musical autonomy, personal autonomy and musical authenticity in relation to musical meaning and informal learning practices within the classroom are discussed.